1990
DOI: 10.1111/j.1468-0092.1990.tb00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Le Corps Féminin Et Son Langage Dans l'ART Paléolithique

Abstract: Our earliest ancestor, homo sapiens sapiens, appeared at the beginning of the Upper Palaeolithic period, and was responsible for the earliest known artistic3gurative representations, among them figures of human beings. We believe, with Leroi-Gourhan, that figurative art obeys the same laws and has the same aims as speech, and that it should be analysed in the same way as language. This language can be natural or conventional, morphological, postural or mimic; it allows us to recognise in different instances re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although their social role is unclear, phallic symbols have been discussed in terms of group cohesion, individuation, and identity, or associated with general considerations around the emergence of social complexity, and the materialized aspects of symbolic thought, gender relations, and sexuality 70,[84][85][86][87][88] . It is difficult to associate a specific function or meaning with the T21 pendant, but we note that current studies of human anthropomorphic sexed imagery-including the several hundred stone, bone, ivory, and antler anthropomorphic figurines known from a wide geographic and temporal range later in the UP [89][90][91][92][93][94][95] -seek to identify particular patterns of spatial and temporal variability and propose interpretations far beyond the dual matriarchy/patriarchy myth 63,68,91,96 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Although their social role is unclear, phallic symbols have been discussed in terms of group cohesion, individuation, and identity, or associated with general considerations around the emergence of social complexity, and the materialized aspects of symbolic thought, gender relations, and sexuality 70,[84][85][86][87][88] . It is difficult to associate a specific function or meaning with the T21 pendant, but we note that current studies of human anthropomorphic sexed imagery-including the several hundred stone, bone, ivory, and antler anthropomorphic figurines known from a wide geographic and temporal range later in the UP [89][90][91][92][93][94][95] -seek to identify particular patterns of spatial and temporal variability and propose interpretations far beyond the dual matriarchy/patriarchy myth 63,68,91,96 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Social divisions between genders have also been identified in the Upper Palaeolithic parietal art from Western Europe. Duhard (1990Duhard ( , 1993 and Rice and Paterson (1988) have both concluded that females are depicted in passive scenes contrasting with males who are shown in active scenes. Rice and Paterson (1988) suggest further that when human groups are shown they are always of the same gender and that the economic role of males is suggested by their association with animals known to be eaten but the economic roles of females are not shown.…”
Section: ■ Symbolic Evidence For Gendermentioning
confidence: 99%
“…Renfrew (1974) once contrasted British Neolithic 'group-oriented' chiefdoms with the 'individualizing' chiefdoms of the succeeding Early Bronze Age. From an even earlier time period, McDermott (1996) has argued that European Upper Palaeolithic female figurines were attempts at self representation, whilst Duhard (1990; has suggested that each figurine may have represented an actual individual. Renfrew (1994,167-70) recently has attempted to link the emergence of the concept of value and the inception of metallurgy in Bronze Age Europe and the Aegean with the development of high-prestige individuals, notably warriors, citing the symbolic display of daggers and other weapons in European mortuary contexts, or high-value commodities in the Aegean realm.…”
Section: Individual Bodiesmentioning
confidence: 99%